NARCISSISM IN LOCAL BUDGETING: THE MIRROR AND MASK EFFECTSOF PUBLIC ASPIRATION FUND - Pasoloran, Oktavian; Sukoharsono, Eko Ganis; Said, Darwis; Rura, Yohanis (The International Journal of Accounting and Business Society, 2015)
This study aims to interpret public aspiration fundin local budgeting in narcissism perspective. Discourse about "public aspiration fundâ€is a reality in budgeting leading to a contradiction, so the question is whether" public aspiration fund" that shows the reality in which the amount of funds used for realizing programs or activities in local government expressespublic needs and aspiration or contains another meaning related to personal interest and certain group interest. The research results provide an understanding that local budgets have potential to accentuate the "hall of mirrors". Public aspiration funds were created bybudgeting actors to express their identity as "the representatives" and to entrust the management to bureaucrats to "serve" public interests. However, in reality, the public aspiration funds have been part of an effort to serve their interests. The public aspiration fundhas become a simulacrumthat produces allthe fake deviated from the reference and create a mark as a mask, camouflage, or a mirage. Keywords: narcissism, budgeting, public aspiration funds, mirrors, masks